2019
DOI: 10.1123/ijsnem.2018-0273
|View full text |Cite
|
Sign up to set email alerts
|

SPRINTING. . . Dietary Approaches to Optimize Training Adaptation and Performance

Abstract: Although sprint athletes are assumed to primarily be interested in promoting muscle hypertrophy, it is the ability to generate explosive muscle power, optimization of power-to-weight ratio, and enhancement of anaerobic energy generation that are key outcomes of sprint training. This reflects the physique of track sprinters, being characterized as ecto-mesomorphs. Although there is little contemporary data on sprinters dietary habits, given their moderate energy requirements relative to body mass, a carbohydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 69 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…Indeed, it has been known for nearly a century that 100% CHO produces ∼5.5% more ATP per liter of oxygen consumed than compared with 100% fat oxidation (Krogh & Lindhard, 1920). Therefore, the achievement of high CHO availability (defined as CHO stores available to provide the substrate needs of an event or training session) is a key goal of competition nutrition and the reader is directed to reviews of the individualized competition needs across events in track and field (Burke et al, 2019;Costa et al, 2019;Slater et al, 2019;Stellingwerff et al, 2019;Sygo et al, 2019). In addition to promoting training quality, undertaking sessions with high CHO availability can enhance the pathways of oxygen-independent glycolysis and CHO oxidation (Cox et al, 2010).…”
Section: Strategies To Promote Cho Utilization During Exercisementioning
confidence: 99%
“…Indeed, it has been known for nearly a century that 100% CHO produces ∼5.5% more ATP per liter of oxygen consumed than compared with 100% fat oxidation (Krogh & Lindhard, 1920). Therefore, the achievement of high CHO availability (defined as CHO stores available to provide the substrate needs of an event or training session) is a key goal of competition nutrition and the reader is directed to reviews of the individualized competition needs across events in track and field (Burke et al, 2019;Costa et al, 2019;Slater et al, 2019;Stellingwerff et al, 2019;Sygo et al, 2019). In addition to promoting training quality, undertaking sessions with high CHO availability can enhance the pathways of oxygen-independent glycolysis and CHO oxidation (Cox et al, 2010).…”
Section: Strategies To Promote Cho Utilization During Exercisementioning
confidence: 99%
“…Therefore, higher energy and macronutrient intake is needed to meet the losses from energy expenditure, replenish glycogen stores, build muscles and repair tissues [2]. Suitable key recommendations and dietary strategies have been made with regard to energy and macronutrients for endurance athletes [3,4], game sports [5,6], strength and power sports [7,8], and track and field athletes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Our data revealed that middle-distance runners considered protein to be a more important macronutrient compared with sprinters. This is an interesting result since, for many years, strength-power athletes, but not middle-distance runners, have been encouraged to have high-protein diets [ 29 ] and, in a previous study, power/sprint athletes were more likely to follow a high-protein diet compared to other athletes [ 21 ]. Nevertheless, both groups rely on the intake of carbohydrates and protein in the hours after the competition to recover between multiple races [ 17 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%